Searching services "on the web": A public web services discovery approach - Wu, Chen; Chang, Elizabeth (IEEE, 2007)
With the surge of Service-Oriented Architecture (SOA) and Web services, service discovery has become increasingly crucial. Public Web services that are available "on the Web" provide unlimited values for a great number of online service consumers anddevelopers. However, the public UDDI Business Registry - the primary service discovery mechanism over the Internet - has been shut down permanently since 2006. This has raised serious problems for public Web services discovery. In this paper, we propose a WSDL-based public Web service discovery approach. It provides a simple-to-use yet effective Web service discovery mechanism that can retrieve relevant Web services directly from the Internet to suffice various requirements. The major contributions of this paperinclude: (1) a review on the state-of-the-art WSDL based Web services discovery approaches; (2) the unique WSDL crawling and manipulation algorithms catering for the Vector Space Model, and (3) a proofof-concept prototype - an online Web services searchengine - an online Web services search engine - based on the proposed approach.